Kinerja Kamera Digital Refleks Lensa Tunggal dengan Sistem Four Thirds - Hendrie Hartono (Bina Nusantara University, 2011)
The core design concept of the 4/3 (Four Thirds) system is to facilitate optimization of the size, performance, of digital cameras and lenses. In addition, a standardized lens mount allows photographers to freely combine interchangeable lenses and cameras from different manufacturers. This is the key feature of the Four Thirds system, the one that makes it possible to explore the full potential of digital photography. The purpose of this research to give description and knowledge about the existence of a new system in digital photography. In the end, this article will be helpful to find out the benefits and disadvantages in using this system and also as comparison with other systems in digital photography.